Pengaruh Rasio C/N dan Penambahan Mikronutrien (Molybdenum, Mangan, dan Nikel) terhadap Kadar Gas Metan Biogas - Novirina Hendrasarie; Santika Octaviana Putri Br Purba (Prosiding ESEC, 2022)
Biogas is a waste teratment technology that uses natural microorganisms to produce energy that is placed in an airtight space. In biogas production, it is necessary to add nutrients to correct the composition of the organic fraction in the waste to approach its ideal composition. The objective of this study is to determine the effect of adding micronutrients molybdeman 1 mg/L, manganese 1 mg.L, nickel 1 mg/L, and a mixture of three micronutrients 1 mg/L in the biogas formation process. The research was conducted on the mixing of cow dung, vegetable waste, hudrilla verticillate, and water in a batch reactor with a capacity of 5 liters. The parameters used in this research are methane gas content and C/N ratio. The best methane gas contwnt and C/N ratio in this study were obtained in the variation of the assition of a mixture of the three micronutrients for 30 days with values of 68.33% and 29.774% respectively.